SEYYEDHOSSEIN NASR ON ISLAM AND SCIENCE - Rif'at Husnul Ma'afi; Muhammad Fiqih Cholidi (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2019)
ABSTRACTÂ Science and religion are two variables that are warmly discussed by contemporary scientists. John F. Haught for example explains the relationship between religion and science through four phases, namely, conflict, contrast, contact, and confirmation. Between these four phases, John F. Haught himself was in a confirmation position. Likewise Seyyed Hossein Nasr, a Muslim scientist and philosopher, is in the same position as John. This is known from his scientific concept known as Scientia Sacra. This concept is unique from the concept of confirmation or integration of science with religion, especially Islam. Although in the Islamic body there is no conflict between the two, new conflicts arise between the two relations caused by the characteristics of modern science which cause many multidimensional crises. This is what triggers the attitude of Muslims who are indifferent to science. In relation to Islam and science, Nasr has its own model in integrating the two. The model itself departs from the doctrine of cosmology which he considers to be a medicine from the paradigm of modern science: narrow, dark, and divided. The model in integrating science and Islam is to change the paradigm of modern science into the paradigm of Scientia Sacra who sees science as it should. So, science cannot be separated from Islam and must follow the principles in Islam.Keywords: Scientia sacra, integration, absolute reality, multidimensional crisis